SDS-PAGE and IR spectroscopy to evaluate modifications in the viral protein profile induced by a cationic porphyrinic photosensitizer - Costa, Liliana
Reactive oxygen species can be responsible for microbial photodynamic inactivation due to its toxic effects, which include severe damage to proteins, lipids and nucleic acids. In this study, the photo-oxidative modifications of the proteins of a non-enveloped T4-like bacteriophage, induced by the cationic porphyrin 5,10,15-tris(1-methylpyridinium-4-yl)-20-(pentafluorophenyl)porphyrin tri-iodide were evaluated. Two methods were used: sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) and infrared spectroscopy. SDS-PAGE analysis showed that the phage protein profile was considerably altered after photodynamic treatment. Seven protein bands putatively corresponding to capsid and tail tube proteins were attenuated and two other were enhanced. Infrared spectroscopy confirmed the time-dependent alteration on the phage protein profile detected by SDS-PAGE, indicative of a response to oxidative damage. Infrared analysis showed to be a promising and rapid screening approach for the analysis of the modifications induced on viral proteins by photosensitization. In fact, one single infrared spectrum can highlight the changes induced to all viral molecular structures, overcoming the delays and complex protocols of the conventional methods, in a much simple and cost effective way.